An insight into an electro-catalytic reactor concept for high value-added production from crude glycerol: Optimization, electrode passivation, product distribution, and reaction pathway identification. (July 2021) - Khosravanipour Mostafazadeh, Ali; De La Torre, Maria Samantha; Padilla, Yessika; Drogui, Patrick; Brar, Satinder Kaur; Tyagi, Rajeshwar Dayal; Le Bihan, Yann; Buelna, Gerardo; Moroyoqui, Pablo Gortares
Abstract: The biodiesel industry produces around 10% w/w crude glycerol. This product has great potential to be valorized to obtain more valuable chemicals. Among all upgrading techniques of no-valuable crude glycerol, the electrochemical conversion is a promising technology. In this study, the green electrochemical conversion of glycerol into value-added products was investigated and optimized in a batch electro-catalytic reactor with a 450 ml working volume using platinum-based electrodes. The redox of glycerol in different solutions was studied by cyclic voltammetric study, the electrode behaviour was explored under chronopotentiometry/chronoamperometry conditions, the kinetics of glycerol consumption was investigated, and the electrode passivation/deactivation was studied by SEM (Scanning Electron Microscope), EDS (energy-dispersive X-ray spectroscopy), and regression models. The maximum non-acidic (dihydroxyacetone/hydroxyacetone or acetol/glycidol) and organic acids (acetic acid, lactic acid, formic acid) formations were optimized using response surface methodology (RSM). The effects of the treatment time, current intensity, type of anode electrode, pH and glycerol concentration were examined. Products concentrations and distributions, reaction mechanism and pathway were also investigated. The results showed that under strong acidic conditions (HCl; pH = 1.4), the highest solvent production (yield of 55%) was achieved using Pt electrode, at a current intensity of 0.31 A (5 mA/cm 2 ). Graphical abstract: Image 1 Highlights: The electrochemical conversion is a promising approach for valorization of glycerol. SEM/EDS and cyclic voltammetric study were investigated for electrode passivation. This method is simple and works at low temperature and ambient pressure conditions. Electrocatalyst, electrolyte solution, and current density are significant factors. At the galvanometric condition, optimum solvents and organic acids were produced.